Digital Pedagogical Driven ICT Assisted Learning through Informal Settings with Reference to Indian Education System: Exploring the impact and scope of ICT-assisted informal learning in the Indian education system (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India is a place where informal education can drive the percentage of literacy. Digital Learning and ICT assisted teaching learning process in current education system created a platform for covering curriculum objectives in informal learning process, although programs governed by open universities providing print media in abundance but the digitization of the content and the implementation of ICT tools and digital content in private and government organization but the utilization through digital pedagogy can accomplish its learning and performance objective through informal settings as well. Covering of the digital literacy among the trainer and facilitators provide the lifelong learning. There is a great chance to capture the literacy percentage along with quality content and internalization of the concept and curriculum. After School learning can be accomplished by digital pedagogy driven education. Informal education system is a way to capture learner in all age group with respect to other social constraints. In Educational Society formal setting is helpful but it require handheld device like mobile as ICT tools or web access to cover the educational objectives of the curriculum. In this paper we enquired the impact and scope of ICT assisted informal learning.